First-principles calculations for the effect of irradiation-induced point defects on the hydrogen dissolution and diffusion in γ-Al2O3 - Xin-Dong Pan; Xiao-Chun Li; Jing Wang; Rongmei Yu; Chunying Pu; Hai-Shan Zhou; Guang-Nan Luo (Nuclear Materials and Energy)
FeAl/Al2O3 is considered the most promising candidate material for tritium permeation barrier (TPB) due to numerous advantages. γ-Al2O3 phase structure is commonly found in FeAl/Al2O3, and is crucial to its effectiveness. In fusion reactors, high-energy neutrons generate a large number of irradiation-induced defects, significantly affecting the performance of γ-Al2O3. The underlying mechanism is still unclear. This study focuses on the influence of irradiation-induced point defects on the dissolution and diffusion of H in γ-Al2O3 using first-principles theory. Our results show that the irradiation-induced point defect exhibit a strong ability to capture dissolved H atoms, leading to higher hydrogen retention. When dissolved H atoms are captured by vacancy-type defects, the diffusion barrier becomes so high that isolated vacancy-type irradiation-induced point defects can hinder the diffusion of H atoms. This in turn enhances the effectiveness of TPB in preventing H permeation. Furthermore, the impediment effect of Al vacancies on H diffusion in γ-Al2O3 is higher than that in α-Al2O3, whereas O vacancies have the opposite effect, impeding H diffusion in γ-Al2O3 less than in α-Al2O3. However, the diffusion barrier of O interstitial atoms and H as a bound entity is only 0.11 eV, which is even far lower than that in α-Al2O3 (0.44 eV). Therefore, O interstitial atoms can accelerate the diffusion process of H, which can reduce the efficiency of protection against H permeation through γ-Al2O3 TPB. The accelerating effect in γ-Al2O3 is higher than that in α-Al2O3. These findings provide valuable insights into the influence of irradiation-induced point defects on H behavior in γ-Al2O3, which is essential for improving the efficiency of FeAl/Al2O3 tritium permeation barriers.